Facial Candidal Abscess in a Patient with Unknown Type 2 Diabetes Mellitus - Peker, Elif (J Maxillofac Oral Surg, 2014)
INTRODUCTION: Facial candidal abscess is an infection with a fungal cause which was presented in this case such a rarity. We report a rare case of facial abscess due to Candida species in a patient with unknown diabetes. MATERIALS AND METHODS: The patient presented with a longstanding firm swelling which occurred 2 weeks ago and did not show any improvement of healing process in spite of surgical and medical treatments. MRI examinations were conclusive and compatible with abscess, so she underwent surgical intervention. Facial candidal abscess was the final diagnosis. CONCLUSIONS: We concluded that, in persistent abscesses, invasive candidiasis should be considered in the differential diagnosis of bacterial infections as it generally affects individuals with diabetes or general defects in the immune system, or those who use widespread antibiotics and steroids.